2018
DOI: 10.1103/physrevlett.120.129901
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Shrinking of Rapidly Evaporating Water Microdroplets Reveals their Extreme Supercooling [Phys. Rev. Lett. 120 , 015501 (2018)]

Abstract: This corrects the article DOI: 10.1103/PhysRevLett.120.015501.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…The resonances are described in the framework of the Mie-Debye light scattering theory [85], which shows that the observed shift of the resonance peaks ( Figure 5(a)) is directly related to a decrease in the droplet diameter with an increasing distance from the nozzle. Accordingly, the droplet diameter could be directly determined from the Raman shifts of the resonance peaks [26]. The obtained values, shown as filled circles in Figure 5(b), then strongly constrained the Knudsen evaporative cooling model calculation, shown as thick solid line in Figure 5(b).…”
Section: Supercooled Water: the Most Anomalous Liquidsupporting
confidence: 52%
See 3 more Smart Citations
“…The resonances are described in the framework of the Mie-Debye light scattering theory [85], which shows that the observed shift of the resonance peaks ( Figure 5(a)) is directly related to a decrease in the droplet diameter with an increasing distance from the nozzle. Accordingly, the droplet diameter could be directly determined from the Raman shifts of the resonance peaks [26]. The obtained values, shown as filled circles in Figure 5(b), then strongly constrained the Knudsen evaporative cooling model calculation, shown as thick solid line in Figure 5(b).…”
Section: Supercooled Water: the Most Anomalous Liquidsupporting
confidence: 52%
“…The obtained values, shown as filled circles in Figure 5(b), then strongly constrained the Knudsen evaporative cooling model calculation, shown as thick solid line in Figure 5(b). From the corresponding temperature curve plotted in Figure 5(c), a lowest liquid droplet temperature of 230.6 ± 0.6 K was thus inferred at about 28.4 mm from the nozzle, the distance at which a small fraction of the about 6-μm-diameter water droplets were still liquid before they froze to ice [26]. These results unambiguously demonstrate that water's deeply supercooled region can be uniquely probed by employing a micrometre-sized water jet in a vacuum.…”
Section: Supercooled Water: the Most Anomalous Liquidmentioning
confidence: 98%
See 2 more Smart Citations
“…Kim et al concluded that a κ T maximum exists at 229 K. However, extracting κ T requires calculating the droplet temperature, and an extrapolation of density data. This extrapolation of density data and the existence of a κ T maximum have been later debated 26,27 , and the accuracy of the reported temperature put into question 28,29 . Nevertheless, if it exists, the κ T maximum near zero pressure would be compatible with the κ T maxima reported at negative pressure.…”
Section: Introductionmentioning
confidence: 99%